Analysts Influence of Non Performing Financing (NPF), Finance to Deposit Ratio (FDR), and Operating Costs and Operating Income (BOPO) on the Return on Assets (ROA) of PT BPRS in West Java Province During the Covid-19 Pandemic - Putri, Tresna Dayana; Munandar, Eris; Santika, Ganjar (CV. Rayyan Dwi Bharata, 2022)
The purpose of this study is to determine the Effect of Non-Performing Financing (NPF), Finance To Deposit Ratio (FDR), And Operating Costs And Operating Income (BOPO) On The Return On Assets (ROA) Of PT BPRS In West Java Province During The Covid 19 Pandemic. The research method used is Quantitative. This research has limitations in the implementation of its analysis and discussion, which was carried out only on fifteen (15) largest Sharia People's Financing Banks in West Java Province with ownership of financial statements recorded at the Financial Services Authority, and the analysis was carried out during the COVID-19 pandemic, namely 2020 Quarter 1 to 2021 Quarter 4 or in quarter size. Based on the test results, it showed that partially variables (NPF) had a significant effect on (ROA), (FDR) did not have a significant effect on (ROA), (BOPO) had a significant effect on (ROA). Meanwhile, simultaneously the influence of NPF, FDR, BOPO has a significant effect on (ROA) PT BPRS in West Java Province during the Covid-19 pandemic.